Nanoparticle-mediated modulation on growth and yield of soybean under salinity stress : Nanoparticle effects on soybean growth and yield under salinity stress - Akter, Most Tanjina; Mannan, Md Abdul; Mamun, Md Abdullah Al; Akter, Masuma (Annals of Bangladesh Agriculture, 2026)
One of the major problems affecting soybean growth and productivity is salinity stress, which lowers plant height, number of leaves, biomass, and yield, particularly in areas affected by salt. To improve salinity tolerance of soybean and sustain growth, development, and yield, this study examined the potential benefits of foliar spray of Iron (II,III) oxide (Fe3 O4 ), Zinc oxide (ZnO), Titaniun oxide (TiO2 ), and Magnesiun oxide (MgO) nanoparticles (NPs). The pot experiment was laid out at the Department of Agronomy, Gazipur Agricultural University, Bangladesh, during the Rabi season of 2023–2024 following a completely randomised design with three replications. Five nanoparticle treatments - control (no nanoparticles), Fe₃O₄, ZnO, TiO₂, and MgO - each applied at a concentration of 200 ppm, along with two salinity levels [control (0 mM NaCl) and 50 mM NaCl], were used in the experiment. The substantial negative effects of salinity on plant growth and yield was observed. Plant height, number of leaves, total dry weight, and seed yield were decreased by 38%, 56%, 64%, and 54%, respectively compared to the control plants. Nanoparticles mitigated the negative effects of salinity. Among the NPs, ZnO showed the best performance, boosting plant height by 59%, number of leaves by 53%, and seed yield by 46%. whereas biomass reduction was only 19% compared to the non-treated saline affected plants. MgO also improved plant performance under salinity. TiO₂ and Fe3 O₄ showed moderate effects. These results indicate that ZnO and MgO nanoparticles effectively minimised the growth and yield losses of soybeans under salinity. Future studies should elucidate the physiological, biochemical, and molecular mechanisms of NP-mediated salinity tolerance in soybean. Ann. Bangladesh Agric. 29(2): 175-193